(Mis)reading different cultures : interpreting international children's literature from Asia - Amos, Yukari Takimoto; Amos, Daniel Miles (Rowman & Littlefield, 2018)
"The book provides relevant theoretical and empirical research findings to address the challenges teachers face when interpreting and teaching with international children's literature from Asia. Strategies are provided relating to how teachers can be more culturally conscious of their own biases and develop culturally appropriate interpretations"--